China's Impact on the African Renaissance The Baobab Grows - Jonker, Kobus (Springer Singapore, 2018)
This book provides the first comprehensive academic study of what China's trade with, and investment in, African countries mean for the socio-economic well-being of the continent. Based on the African Tree of Organic Growth Framework developed in the book, Jonker and Robinson outline the factors necessary in realizing Africa's Renaissance vision and the impact that the Chinese might have on this process. Using the metaphor of the Baobab tree, the authors analyze the historical, cultural and economic contexts within African countries, the channels available to produce development and growth, and the fruits or social and economic well-being created by this integrated process. The book takes readers on a journey of numerous African examples and case studies, describing and analyzing the challenges and complexities of countries in their desire to achieve organic, cultural, scientific and economic renewal, and the improvement of the well-being of their citizens. This book will be of great value to economists, people who wish to do business in Africa, China-watchers, those who are following the development and growth of Africa, and more. Kobus Jonker is a Professor in Business Strategy and International Business at the Nelson Mandela University Business School in Port Elizabeth, South Africa. He started his academic career in 1989 and pioneered the establishment of the Business School at the Nelson Mandela University in 2005. He has facilitated the strategic planning sessions of several prominent companies and consulted to the senior management of various companies in the past 20 years. He holds a doctoral degree in Business Strategy from the University of Pretoria. Bryan Robinson is a Research Associate and lecturer in Business and Society at the Nelson Mandela University Business School in Port Elizabeth, South Africa. He holds a doctoral degree in Business Administration from the Nelson Mandela University. His research specializes in the fields of business ethics, corporate governance, development economics and globalization. His research into foreign direct investment in Africa takes a specific focus on China's engagement in Africa and its socio-economic impact.